Quality changes in high pressure processed tan mutton during storage - Li, Dongdong (Food science and technology international = Ciencia y tecnologia de los alimentos internacional, 2021)
The current study investigated the effects of high pressure (HP) treatment at 200 MPa and 500 MPa on quality characteristics of post-rigor tan mutton stored for 7 days at 4 °C, and textural changes were monitored during storage by means of the stress relaxation test. Application of 500 MPa high pressure significantly increased the elasticity and stiffness of meat after 7 days of storage (P < 0.05), accompanied by a lighter and less red appearance and markedly enhanced centrifugal loss during storage campared to untreated (P < 0.05). High pressure treatment at 200 MPa also substantially increased the lightness of samples throughout storage (P < 0.05), and showed a significant increase in stiffness at the end of storage (P < 0.05). Immunoblotting and electrophoresis (SDS-PAGE) analysis of key structural proteins revealed that myosin heavy chain denaturation began at 200 MPa, while actin denaturation occurred at 500 MPa. Troponin-T was continuously degraded in different treatments as storage progressed, and 200 MPa treatment and untreated represented similar degradation patterns, while 500 MPa treatment displayed more intense intact troponin-T at 38 kDa degradation. Results suggest that HP induced changes in cytoskeleton proteins, thereby affecting texture, water holding properties and lightness